Difference and Analysis of Evaluating Psychological Monitors' Interview and Classmates' Being Interviewed About Suicide - Zhan, Qisheng; Xia, Tianyu (Frontiers in Psychology, 2022)
In recent years, suicide has become the leading cause of unnatural death among college students in China. Psychological monitors, as class cadres who manage affairs related to mental health within their classes, are critical in identifying and intervening in psychological crises among their classmates. In China, however, talking about death is a cultural taboo, and many mental health workers have expressed concern about their implementation of interviews about suicide with others. Generally speaking, interviews with suicidal classmates are usually conducted by professional psychological experts and psychological monitors (psychological monitors are non-professional peer counselors in China). Such classmates that have undergone both the aforementioned types of interviews were investigated in this paper. However, this paper focuses on two issues. Firstly, what are the perceptions of classmates who have been interviewed toward the experience of being interviewed by psychological monitors? Secondly, what are the psychological monitors' perceptions of their implementation of interviews about suicide with classmates? In this study, 1664 classmates who had been interviewed and 1320 psychological monitors were surveyed by means of an online questionnaire. The results showed that classmates who have been interviewed perceived their experience of being interviewed by a psychological monitor about suicide more positively than the psychological monitors who viewed their implementation of interviews about suicide with classmates. Among the classmates who have been interviewed, three categories of classmates have more positive perceptions of their experience of being interviewed by a psychological monitor about suicide. Category one is males. Category two is those who were willing to seek help from the psychological monitors. Category three is those who had a more correct attitude toward mental illness. Among the psychological monitors, three categories of psychological monitors have more positive perceptions of their implementation of interviews about suicide with classmates. Category one is those who have the experience of implementing interviews with their classmates. Category two is those who have received training. Category three is those who had a more correct attitude toward mental illness. Psychological monitors can interview classmates confidently, and the training of psychological monitors on mental health knowledge should be strengthened in the universities.